Desempenho de gotejadores com uso de esgoto doméstico tratado - Pletsch, Talita Aparecida [UNESP]; Cruz, Raimundo Leite [UNESP]; Mazzer, Helton Rogério; de Oliveira, Érika Fabiana [UNESP] (My University, 2009)
This paper aimed to determine the flow rate of drippers, their flow rate-pressure curve, their equation, their flow rate variation coefficient (VCq), as well as to evaluate the uniformity of water application of the Netafim drip pipe, Tiran 17 model, used for irrigation with domestic wastewater from treated household drain. After 1000 working hours, the blockage of some drippers decreased the uniformity of water application from 98% to lower than 60% and increased the flow variation coefficient to values higher than 0.29.
Performance of drippers using treated domestic wastewater
Keywords: Flow rate variation coefficient; Wastewater; drip irrigation; flow field; flow measurement; performance assessment; wastewater; water flow; water treatment